Distinctive patterns on CT angiography characterize acute internal carotid artery occlusion subtypes. Issue 5 (February 2017) - Hong, Ji Man; Lee, Sung Eun; Lee, Seong-Joon; Lee, Jin Soo; Demchuk, Andrew M.
Abstract : Abstract: Noninvasive computed tomography angiography (CTA) is widely used in acute ischemic stroke, even for diagnosing various internal carotid artery (ICA) occlusion sites, which often need cerebral digital subtraction angiography (DSA) confirmation. We evaluated whether clinical outcomes vary depending on the DSA-based occlusion sites and explored correlating features on baseline CTA that predict DSA-based occlusion site. We analyzed consecutive patients with acute ICA occlusion who underwent DSA and CTA. Occlusion site was classified into cervical, cavernous, petrous, and carotid terminus segments by DSA confirmation. Clinical and radiological features associated with poor outcome at 3 months (3–6 of modified Rankin scale) were analyzed. Baseline CTA findings were categorized according to carotid occlusive shape (stump, spearhead, and streak), presence of cervical calcification, Willisian occlusive patterns (T-type, L-type, and I-type), and status of leptomeningeal collaterals (LMC). We identified 49 patients with occlusions in the cervical (n = 17), cavernous (n = 22), and carotid terminus (n = 10) portions: initial NIH Stroke Scale (11.4 ± 4.2 vs 16.1 ± 3.7 vs 18.2 ± 5.1; P  < 0.001), stroke volume (27.9 ± 29.6 vs 127.4 ± 112.6 vs 260.3 ± 151.8 mL; P  < 0.001), and poor outcome (23.5 vs 77.3 vs 90.0%; P  < 0.001). Cervical portion occlusion was characterized as rounded stump (82.4%) with calcification (52.9%) and fair LMC (94.1%); cavernous as spearhead occlusion (68.2%) with fair LMC (86.3%) and no calcification (95.5%); and terminus as streak-like occlusive pattern (60.0%) with poor LMC (60.0%), and no calcification (100%) on CTA. Our study indicates that acute ICA occlusion can be subtyped into cervical, cavernous, and terminus. Distinctive findings on initial CTA can help differentiate ICA-occlusion subtypes with specific characteristics.